Escape of tumor cells from the NK cell cytotoxic activity. Issue 4 (15th September 2020) - Cantoni, Claudia; Wurzer, Hannah; Thomas, Clément; Vitale, Massimo
Abstract: In recent years, NK cells, initially identified as potent cytotoxic effector cells, have revealed an unexpected complexity, both at phenotypic and functional levels. The discovery of different NK cell subsets, characterized by distinct gene expression and phenotypes, was combined with the characterization of the diverse functions NK cells can exert, not only as circulating cells, but also as cells localized or recruited in lymphoid organs and in multiple tissues. Besides the elimination of tumor and virus-infected cells, these functions include the production of cytokines and chemokines, the regulation of innate and adaptive immune cells, the influence on tissue homeostasis. In addition, NK cells display a remarkable functional plasticity, being able to adapt to the environment and to develop a kind of memory. Nevertheless, the powerful cytotoxic activity of NK cells remains one of their most relevant properties, particularly in the antitumor response. In this review, the process of tumor cell recognition and killing mediated by NK cells, starting from the generation of cytolytic granules and recognition of target cell, to the establishment of the NK cell immunological synapse, the release of cytotoxic molecules, and consequent tumor cell death is described. Next, the review focuses on the heterogeneous mechanisms, either intrinsic to tumors or induced by the tumor microenvironment, by which cancer cells can escape the NK cell-mediated attack. Graphical Abstract: Review on the mechanisms by which the tumor microenvironment evades the NK cell-mediated cytotoxic response.